Hard facts, dangerous half-truths, and total nonsense : profiting from evidence-based management - Pfeffer, Jeffrey. (Harvard Business School Press, 2006)
"Through evidence-based management, business leaders face the hard facts and act on the best evidence - trumping the competition. They also view common beliefs about effective management with healthy skepticism. To demonstrate the dangers lurking in such beliefs, the authors dismantle six widely held - but ultimately flawed - half-truths in core management areas including leadership, strategy, change, talent, incentives, and the connections between work and the rest of life. Pfeffer and Sutton describe how to identify and apply practices that are best for their companies, rather than blindly embrace what seems to have worked elsewhere."--BOOK JACKET.